Robust speed control of permanent magnet synchronous motors using model predictive and sliding mode strategies - Magdy Meawad; Abdelsalam A. Ahmed; Mona I. Abdelkader; Yasser G. Dessouky (PLoS ONE, 2026)
This paper presents robust speed-control techniques for permanent-magnet synchronous motors (PMSMs) by integrating model-predictive and sliding-mode strategies. Two controllers are developed: a Sliding-Mode Speed Control–based Model Predictive Current Controller (SMSC-MPCC) using an Adaptive Sliding Mode Surface (ASMS) and an Adaptive Improved Exponential Reaching Law (AIERL), and a Model Predictive Direct Speed Controller (MPDSC) incorporating a Sliding-Mode Load Torque Observer (SMLTO) and a Sliding-Mode Disturbance Observer (SMDO) for sensorless operation and delay compensation. The methods are analyzed under explicit disturbance and saturation assumptions, and their stability is established via Lyapunov arguments. Extensive simulations were conducted, encompassing low-speed operation, frequency-sweep tracking, and Monte Carlo–based robustness evaluation under parameter variations. Performance is assessed using rise time, settling time, overshoot, steady-state error, ITAE, chattering index, and closed-loop bandwidth. Simulated tests confirm statistically significant improvements in mean ITAE and stability margin for the proposed SMSC-MPCC across operating conditions, while MPDSC achieves the fastest disturbance recovery with sensorless capability. The results provide a practical pathway to robust, low-chattering speed control under uncertainty, and clarify the trade-offs among predictive sliding-mode designs for PMSM drives.